Embracing uncertainties: The paradox of environmental education within formal education - Jane Burt (Environmental Association of Southern Africa, 1998)
This paper is a pair of binoculars which I have used to scan the last two years that I have been studying environmental education, the focus being on the research I did on Theatre for Development for environmental education in formal education. The paper aims to bring into view some on the paradoxes of doing environmental education within the structure of formal education from the tragic position of post-modern intellectual thought. I ask whether a critical approach to environmental education can exist within the current structure of formal education? I question whether environmental education can be viewed as a fixed product (be this a positivistic or critical product) within a formal structure and instead call for environmental education to be viewed as reflexive experience.